General insights on obstacles to dog vaccination in Chad on community and institutional level - Mbaipago, Nodjimbadem; Madjadinan, Alladoumngar; Amalaman, Djedou Martin; Andrée Ndour, Prisca; Zinsstag, Jakob; Heitz-Tokpa, Kathrin; Lechenne, Monique (Frontiers in Veterinary Science, 2022)
Domestic dogs are responsible for 95% of all human rabies cases worldwide and continue to be the main reservoir for this fatal virus in African and Asian countries. Interrupting the spread of the disease in the domestic dog population is therefore necessary for long-term, sustainable rabies control. Chad has been recognized as a rabies-endemic country since 1961, but no national control strategy is in place to date and dog vaccination coverage is very low. This qualitative, descriptive study aims to describe the main barriers to dog vaccination on both the community and the institutional level from a socio-anthropological point of view in Chad. The study was embedded in an overall project conducted from 2016 to 2018, to determine rabies burden and vaccine demand in West and Central Africa, funded by GAVI, the vaccine alliance. Data collection was conducted on the occasion of the project's closing workshops with stakeholders organized between August to September 2018 in the four (4) project areas: Logone Occidental, Ouaddaï, Hadjer Lamis and Chari Baguirmi. We conducted interviews and focus group discussions (FGD) among veterinary officers and dog owners. Participants were selected purposively based on their place of residence (dog owners) or work place (veterinary officers) and their previous contact with the project through reporting (dog owner) or management (veterinary officers) of a suspect dog rabies case. In each region, one FGD was organized with dog owners, and one FGD with heads of veterinary posts. At the end of the FGDs, a few participants were randomly selected for interviews. In addition, in each region an interview was conducted with the head of the livestock sector, the chief district medical officers and the head of a civil society association. The identified barriers to dog vaccination access are grouped into three main aspects: the economic, the socio-cultural and the institutional level. Economic constraints encountered relate to the cost of the vaccine itself and the expenses for transporting the dogs to the vaccination site. The cultural belief that the vaccine will have an impact on the therapeutic properties of dog meat for consumers (observed in Southern Chad), and the fact that dogs are considered impure animals in Muslim faith, which prohibits handling of dogs, are obstacles identified on the sociocultural level. At the institutional level, the unavailability of vaccines in veterinary services, the lack of communication about the law on dog vaccination, the absence of rabies in the training curricula of veterinary agents, and the lack of intersectoral collaboration limit vaccination coverage. In order to improve vaccination coverage and rabies surveillance with a view to eradicate rabies by 2030, communication strategies that are adapted to the context and that take cultural obstacles into account must be put in place in a synergy of interdisciplinary action. In addition, factors such as affordability, geographical access and availability of dog rabies vaccines needs to be addressed throughout the country. Although our study design did not allow a detailed analysis of obstacles related to socio-economic level, gender and age the broad insights gained can provide general guidance for future interventions in Chad and similar countries.